Pendampingan Implementasi Digital Branding Pada UMKM Krepek Tempe di Desa Sumber Kejayan Kecamatan Mayang Kabupaten Jember - Ningrum, Intan; Jamil, Diana Akmaliyah; Handayani, Ayu Nurita; Apriliana, Silfi Putri; Susanto, Yuda; Andriansyah, Aldrien; Luthfiyah, Lenny (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Sumber Kejayan Village is one of the villages in Mayang District which has a livelihood as a farmer. In Krepek Tempe UMKM , there is a problem, namely the lack of ability to use technology nowadays, so the ability of UMKM to carry out marketing is limited. The aim of this service is to introduce Krepek Tempe products to a wider market by assisting with the implementation of digital branding such as packaging development, creating a product logo. In this service, the methods used are observation, socialization, discussion and brand design, training and mentoring for Krepek Tempe UMKM actors. From the activities carried out, Krepek Tempe products have become more attractive and of course can have a positive impact and improve the economy of local village residents.